#### Answer

The solution is $\frac{11}{16}$

#### Work Step by Step

7z + $\frac{1}{16}$ - 6z = $\frac{3}{4}$ Simplify 7z-6z=z
z +$\frac{1}{16}$ = $\frac{3}{4}$
Subtract $\frac{1}{16}$ to both sides
z +$\frac{1}{16}$ - $\frac{1}{16}$ =$\frac{3}{4}$ - $\frac{1}{16}$
LCD of 4 and 16 is 16
z=$\frac{12}{16}$ - $\frac{1}{16}$
z=$\frac{12-1}{16}$
z=$\frac{11}{16}$
The solution is $\frac{11}{16}$
Check
7z +$\frac{1}{16}$ -6z=$\frac{3}{4}$
7$\times$$\frac{11}{16}$ +$\frac{1}{16}$ -6$\times$$\frac{11}{16}$=$\frac{3}{4}$
$\frac{77}{16}$ +$\frac{1}{16}$ -$\frac{66}{16}$=$\frac{12}{16}$
$\frac{77+1-66}{16}$=$\frac{12}{16}$
$\frac{12}{16}$=$\frac{12}{16}$